New species and findings of Pagastia Oliver (Diptera: Chironomidae: Diamesinae) from Central Asia, with DNA barcoding of known species of the genus - Makarchenko, Eugenyi A.; Semenchenko, Alexander A.; Palatov, Dmitry M. (Zootaxa, 2021)
Chironomids of the genus Pagastia Oliver (Diamesinae, Diamesini) from the mountains of Central Asia are revised using both morphological characters and molecular data. Illustrated descriptions of the adult male Pagastia (P.) caelestomontana sp. nov. from Kirgizstan and Tajikistan, P. (P.) hanseni sp. nov. from Tajikistan, and record of a finding apparently a new species P. (P.) aff. lanceolata (Tokunaga) from Tajikistan as well as an updated a key to the determination of the adult males of all known species of Pagastia are provided. A phylogenetic framework is reconstructed based on two mitochondrial genes cytochrome oxidase subunit I (COI) sequences of 34 samples belonging to 7 species of the genus Pagastia and cytochrome oxidase subunit II (COII) available for most samples. Phylogenetic trees of some known species of the genus Pagastia were reconstructed using the combined dataset and Bayesian inference (BI) and Maximum Likelihood (ML) methods. The interspecific K2P distances between seven Pagastia species including P. (P.) caelestomontana sp. nov., P. (P.) hanseni sp. nov. and undescribed P. (P.) aff. lanceolata (Tokunaga) are 6.3–13.2 which corresponding to species level.